Feasibility of growing Stevia (Stevia rebaudiana) at Jabal Al-Akhdar, Sultanate of Oman - Salim Ali Al-Rawahi; Amna Mahmoud Al-Toobi; Mohammed Issa Al-Balushi (Journal of Agricultural and Marine Sciences, 2018)
Oman is one of the top nine countries in the world with highest prevalence of diabetes. There is therefore more awareness among the people to take necessary precautions to preserve their health by reducing their sugar consumption and replacing it with low calorie sweeteners. Stevia is a natural herbal sweetener that is safe and does not have the neurological or renal side effects associated with some of the artificial sweeteners. A feasibility study to grow Stevia was undertaken after obtaining the seeds that were initially planted in greenhouse to study their growth habits under controlled conditions. The plants were then transferred to the field in Jabal Al-Akhdar at an elevation of 1079 m above sea level where temperatures were appropriate for Stevia growth in summer since it was within its tolerant temperature range. Two types of Stevia plants were transferred to JA for the three months field study; those that originated directly from seeds and those from transplant cuttings. Drip irrigation system with timer was installed with two laterals each having six emitters spaced 60 cm apart and each supplying 2 liters of water per day. Moderate fertilizer NPK was applied. Five out of six plants in each of the two plots grew very well to the end of the season. Some insects were attracted by the sweetness of the leaves but proper measures were taken to prevent damage. Results show that it is feasible to grow Stevia in JA in summer.